STRATEGI BPR DALAM MENGHADAPI GEMPURAN FINTECH - Nyoman Rajendra Kumara; I Gusti Ngurah Putra Suryanata (Master of Management, Mataram University, 2023)
Rural Banks (BPR) are banks that carry out business activities conventionally or based on syariah principles which in their activities do not provide services in payment traffic. The activities of BPRs are much narrower than those of commercial banks because BPRs are prohibited from accepting demand deposits, foreign exchange and insurance activities. The role of BPR has a significant contribution to the economy in Indonesia. Based on the Indonesian Banking Statistics released by the OJK, the number of rural banks in Indonesia continues to decline. On the other hand, the development and growth of Fintech (Financial Technology) is very fast. The rapid growth of fintech is because this service offers various advantages to make financial transactions more effective and efficient. Based on this, there is an imbalance between the growth of BPR compared to the growth of fintech in Indonesia. Both BPR management and shareholders must anticipate changes and challenges to the BPR business going forward. This study uses a qualitative method by conducting in-depth interviews with BPRs and fintech representatives. The results of the research can be used as a reference both by shareholders and BPR management so that they can continue to survive and grow Keywords: Fintech, BPR, Strategy